Assessment of patients with periorbital melanosis for hyperinsulinemia and insulin resistance - Devinder M Thappa; Laxmisha Chandrashekar; Medha Rajappa; R Usha; K Muthupandi; Palani S Mohanraj; Malathi Munisamy; Nidhi Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Periorbital melanosis (PM) is one of the most common dermatological condition seen in routine practice. Several cutaneous markers such as acanthosis nigricans have been associated with insulin resistance (IR). However, the association of PM with IR needs to be substantiated. Objective: The objective of the study is to evaluate the association of circulating adipokines and IR with PM. Materials and Methods: In this cross-sectional study, we recruited 100 patients with PM and 100 age- and gender-matched healthy controls. The serum levels of leptin, adiponectin, fasting glucose, fasting insulin, insulin-like growth factor-1 (IGF-1), homeostatic model assessment of insulin resistance (HOMA-IR), and leptin: adiponectin ratio (L/A ratio) were assayed. Results: The serum levels of leptin, fasting glucose, fasting insulin, HOMA-IR, L/A ratio were significantly higher in patients with PM as compared to controls. The serum levels of adiponectin were significantly lower in cases as compared to controls. On multivariate regression analysis, leptin, adiponectin, and HOMA-IR were found to be significant, even after adjusting for BMI, blood pressure and LDL and HDL cholesterol.Conclusion: Our findings suggest that patients with PM have hyperinsulinemia, IR, and elevated L/A ratio. PM as a marker of IR in adults may help in identifying patients early and thus aid in the early prevention and management of the disease.